2017
DOI: 10.1371/journal.pone.0177582
|View full text |Cite
|
Sign up to set email alerts
|

Phenological changes in bamboo carbohydrates explain the preference for culm over leaves by giant pandas (Ailuropoda melanoleuca) during spring

Abstract: Seasonal changes in the foodscape force herbivores to select different plant species or plant parts to meet nutritional requirements. We examined whether the search for calorie-rich carbohydrates explained giant panda’s selection for bamboo culm over leaves during spring. Leaves and culms were collected from four Phyllostachys bamboos (P. aurea, P. aureosulcata, P. glauca, and P. nuda) once per month over 18–27 months. Monthly changes in annual plant part nutrients were examined, and compared to seasonal forag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…Pandas are extremely selective upon choosing which bamboo component to eat (i.e., shoots, leaves, branches, or stem) (Dierenfeld et al, 1982;Mainka et al, 1989;Edwards et al, 2006). Leaves are generally consumed all year long, however, a typical peak in stems consumption between March and May has been observed (Hansen et al, 2010;Williams et al, 2013;Knott et al, 2017) in both captive and wild pandas (Schaller et al, 1985;Taylor and Zisheng, 1987;Rybiski Tarou et al, 2005). As bamboo is an evergreen plant with leaves available throughout the year, the exact biological mechanisms motivating a dietary shift to stems remains unexplained.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pandas are extremely selective upon choosing which bamboo component to eat (i.e., shoots, leaves, branches, or stem) (Dierenfeld et al, 1982;Mainka et al, 1989;Edwards et al, 2006). Leaves are generally consumed all year long, however, a typical peak in stems consumption between March and May has been observed (Hansen et al, 2010;Williams et al, 2013;Knott et al, 2017) in both captive and wild pandas (Schaller et al, 1985;Taylor and Zisheng, 1987;Rybiski Tarou et al, 2005). As bamboo is an evergreen plant with leaves available throughout the year, the exact biological mechanisms motivating a dietary shift to stems remains unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of the waxy outer cover from culms to get access to the softer, yellow pith before ingestion is a common behavior also in the wild (Schaller et al, 1985), and possibly linked to bamboo composition. A present assumption considers seasonal variation in bamboo nutrient content a reason for pandas' dietary behavior (Knott et al, 2017). However, it appears counterproductive to forage on the less digestible, woody pith during the panda's breeding season (March to April), when extra energy is spent to seek mates (Wildt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mucus occurrence peak in October might possibly be related to the diet transition from culm to leaves due to the feeding preferences of the pandas in this study, which may cause an increased occurrence of mucus excretion [4,5]. In addition, a feeding behavior study showed that the leaf was the primary plant part consumed from June to December, whereas culm was consumed primarily from February to May [24]. Another nutrition experiment showed that the total fiber was always greater in the culm than in the leaves throughout the year [25].…”
Section: Discussionmentioning
confidence: 99%
“…There is wide variation in the availability and nutritional composition of foods in nature, and thus animals are often faced with deficient or imbalanced diets. As a consequence, many animals have evolved diet regulation behaviors to maintain a balanced nutrient intake (Knott et al., ; Simpson, Sibly, Lee, Behmer, & Raubenheimer, ). Yet, in some cases, restricted diet choices or food availability may limit the ability of animals to regulate their macronutrient intake to their desired or target levels (Moore, Wiggins, Marsh, Dearing, & Foley, ; Simpson et al., ).…”
Section: Introductionmentioning
confidence: 99%